Strontium isotopic composition of the Po river dissolved load: Insights into rock weathering in Northern Italy. (October 2018) - Marchina, C.; Natali, C.; Fahnestock, M.F.; Pennisi, M.; Bryce, J.; Bianchini, G.
Abstract: Strontium isotopic composition ( 87 Sr/ 86 Sr) of river water provides insight on the nature of rocks involved in the weathering processes and important constraints for reconstructing silicate versus carbonate weathering in large scale basins. New data, presented in the context of a geochemical map of the Po river basin, highlight that the Po river water evolves from the upper part of the catchment, where 87 Sr/ 86 Sr approaching 0.7097 relates to the weathering of igneous and metamorphic silicate rocks, to the middle part, where less radiogenic compositions ( 87 Sr/ 86 Sr ∼ 0.7089) are driven by the confluence of the tributaries draining Mesozoic carbonate rocks of the South Alpine domain and from inflow of Apennine streams characterized by less radiogenic Sr signatures due to weathering of marly sediments and mafic magmatic rocks. Down flow, the Sr isotopic compositions of Po river water rises at 0.7091 either by the confluence of the last Apennine tributary (Panaro, 87 Sr/ 86 Sr ∼ 0.7095) and/or by the possible contribution from hyporheic exchanges. Po river isotopic signatures reveal slightly more radiogenic 87 Sr/ 86 Sr in comparison to other important Alpine river systems (e.g. Danube, Rhine and Rhône), likely suggesting that silicate rocks are comparatively contributing more weathering byproducts in the Po basin. Highlights: 87 Sr/ 86 Sr of the Po river dissolved load was studied for its entire course in different years. Po river water Sr isotopic signatures are slightly more radiogenic than those of other important Alpine river systems. 87 Sr/ 86 Sr suggests a comparatively high weathering of the silicate with respect to carbonate rocks in the Po river basin. More effective weathering rate of silicate rocks could be related to warmer conditions typical of southern Europe.